Evaluation of the Lexington County, South Carolina, Domestic Violence Court, 1997-2002 - Gover, Angela R. ([Verlag nicht ermittelbar], 2005)
A separate Criminal Domestic Violence Court (CDVC) was established in Lexington County, South Carolina, in November 1999, to hold perpetrators of domestic violence accountable through increasing fines and jail time and to place a strong emphasis on mandatory batterer treatment programs. The CDVC was a specialized court that combined the efforts of law enforcement, judges, prosecutors, mental health professionals, and victim advocates to improve the safety of domestic violence victims and hold offenders accountable. The researchers undertook to evaluate and measure the extent to which the CDVC was successful in implementing its goals. For the process evaluation, interviews were conducted in 2002 with 50 victims and 50 defendants to examine their overall level of satisfaction with the court process, their perceptions of procedural justice, and their recommendations for improving the CDVC process. Interviews were conducted in person using structured questions immediately after a case was heard. The outcome evaluation consisted of two methods of data collection. A time series intervention analysis examined the monthly frequency of criminal domestic violence for the years 1997 through 2001. Criminal domestic violence cases were compared for the 34 months before the establishment of the CDVC (January 1997 to October 1999) and the first 26 months following its implementation (November 1999 to December 2001). Additionally, in an effort to examine the impact of the Lexington County Criminal Domestic Violence Court on individual case outcomes, a recidivism analysis was conducted on a random sample of 400 criminal domestic violence cases. Of these cases, 200 were control cases drawn from the Lexington County Sheriff's Department's arrest database for the period January 1997 to June 1999, and 200 were treatment cases comprised of domestic violence arrest cases that occurred between December 1999 and December 2000 and processed through CDVC. Variables in Part 1 (Victim Interview Data) and Part 2 (Defendant Interview Data) included responses to structured interview questions about the victims' and offenders' perceptions of various aspects of the court process, whether they felt treated with dignity and respect, and their overall impression of the CDVC response to domestic violence. Variables in Part 3 (Monthly Arrest Data) include court period, month, and frequency of monthly domestic violence arrests, monthly simple assault arrests, and monthly aggravated assault arrests. Variables in Part 4 (Recidivism Data) include race, age, and gender of offender, employment status, booking date, days in jail prior to trial, number of charges pending, number of prior domestic violence offenses, date of first re-arrest, recidivism within first year and a half, days free of arrest, if defendant was diverted to pretrial intervention, and the amount of the fine.